Capital Markets and Financial Intermediation in the Baltic States. (IMF Staff Country Reports; Country Report ;, 2003)
This paper analyzes the capital markets and financial intermediation in the Baltic States. It provides a comprehensive overview of the structure and level of development of the financial system, discussing some of the unique characteristics of the Baltics, such as leasing; and comparing the structure of the Baltic financial systems to other European Union accession countries and/or euro zone averages, both of which serve as benchmarks. The paper also addresses some of the broader analytical questions concerning how the financial system might be developed in the Baltics.